2018
DOI: 10.35118/apjmbb.2018.026.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Bactofection of SW620 cell by Lactococcus lactis M4

Abstract: In this study, a local dairy isolate, L. lactis M4 was investigated for its ability to be developed as a live delivery vector to deliver plasmid DNA into human colon cancer cell line, SW620. L. lactis M4 strain was found to adhere to and internalize SW620 cells optimally after 2 hours of infection period at a multiplicity of infection 250:1, bacteria per cancer cell. Bacteria also managed to survive intracellularly for 7 hours. Entry into SW620 cells was inhibited by Cytochalasin D and Vinblastine, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(82 reference statements)
1
0
0
Order By: Relevance
“…By avoiding the use of genetic modifications, this approach is expected to comply with the United States Food and Drug Administration (USFDA) requirements for future applications of this strain in human. Findings from this study are also coherent with another study, which also reported on the ability of this local strain to display bacterial interaction with human colorectal cancer cell line, SW620 cells (Faroque et al, 2018). According to Faroque et al (2018), L. lactis M4 showed significantly greater rate of bacterial adherence and internalisation in comparison to an established probiotic strain, Lactobacillus reuteri CI.…”
Section: Bacterial Adherence and Internalisationsupporting
confidence: 89%
“…By avoiding the use of genetic modifications, this approach is expected to comply with the United States Food and Drug Administration (USFDA) requirements for future applications of this strain in human. Findings from this study are also coherent with another study, which also reported on the ability of this local strain to display bacterial interaction with human colorectal cancer cell line, SW620 cells (Faroque et al, 2018). According to Faroque et al (2018), L. lactis M4 showed significantly greater rate of bacterial adherence and internalisation in comparison to an established probiotic strain, Lactobacillus reuteri CI.…”
Section: Bacterial Adherence and Internalisationsupporting
confidence: 89%